SCHOOL PRINCIPAL LEADERSHIP MODEL IN SCHOOL FINANCE MANAGEMENT (CASE STUDY: MIS NURUL ULUM SENDANG ASIH) - Maisaroh, Iis; Umurohmi, Ulfah (STIT AL MULTAZAM, 2023)
The principal's leadership model in school payment management is a concept related to the way the principal manages financial resources in the school in order to maximize the desired results. This concept is based on the understanding that effective leadership is very important in optimizing the use of financial resources in schools. The research methods used are qualitative and quantitative research. In the research process, a survey was conducted to collect data from respondents involved in school financing management. The data obtained is then processed using data processing formulas to obtain relevant and useful information. The research results concluded that the majority of respondents had a positive view of the leadership of school principals in school financing management. However, there are still certain aspects that need to be improved to improve the performance of school principals in managing school finances. It is hoped that this research can contribute to the development of a better and more effective school principal leadership model in school financing management. The conclusion of this research is that good leadership from school principals can increase the effectiveness and efficiency of school financing management, thereby improving the quality of education provided.